2018
DOI: 10.1177/1559325818815031
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Low-Dose Radiation on the Bone Marrow, Lung, and Testis Collected From the Same Exposed BALB/cJ Mice

Abstract: We used 3 biological metrics highly relevant to health risks, that is, cell death, inflammation, and global DNA methylation, to determine the late effects of low doses (0.05 or 0.1 Gy) of 137Cs γ rays on the bone marrow, lung, and testis collected at 6 months post-irradiation from the same exposed BALB/cJ mouse. This integrative approach has not been used for such a purpose. Mice exposed to 0 or 1 Gy of radiation served as a sham or positive control group, respectively. The results could deliver information fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Previous research has linked altered DNA methylation to the development of many diseases including CVD [11,12]. Conversely, ionizing radiation has been shown to cause DNA methylation alterations both in vitro and in vivo [13][14][15][16]. Considering the common occurrence of DNA methylation alterations in CVD and after ionizing radiation exposure, we suggest a previously unaddressed involvement of DNA methylation in radiation-induced CVD.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous research has linked altered DNA methylation to the development of many diseases including CVD [11,12]. Conversely, ionizing radiation has been shown to cause DNA methylation alterations both in vitro and in vivo [13][14][15][16]. Considering the common occurrence of DNA methylation alterations in CVD and after ionizing radiation exposure, we suggest a previously unaddressed involvement of DNA methylation in radiation-induced CVD.…”
Section: Introductionmentioning
confidence: 72%
“…This is because of the varying aims of these studies which range from the investigation of radiation-induced carcinogenesis, radiation-induced genomic instability and bystander effects [13][14][15]95,101,102,109,110] to cellular responses to radiation and radiosensitivity [100,103,104,108]. In addition, some studies addressed the difference between the effects of IR on somatic and germinal tissues [16].…”
Section: Does Radiation Impact Dna Methylation and How?mentioning
confidence: 99%
“…Although many studies opposed it through showing LDR (0.1 and 0.2 Gy) reportedly promoted cell death, inflammation, ROS generation (lipid oxidation), and DNA damage (5-hydroxymethylcytosine); and activated damage responses (p53, p38, p21, ERK1/2, NF-κB, TGF-β, etc.) in the lung, these studies unanimously agreed that certain irradiation conditions resulted in less severe changes in lung than that in the liver and the spleen ( Sypin et al, 2003 ; Avti et al, 2005 ; Lee et al, 2006 ; Kim et al, 2007 , 2015 ; Hong et al, 2014 ; Jangiam et al, 2018 ). Moreover, the protective roles of LDR in the lung have been demonstrated in various stress models.…”
Section: The Organ-specific Effects Of Ldr In Cell and Mouse Modelsmentioning
confidence: 82%
“…Many studies have shown that the lung ranks among the organs that are most resistant to LDR damage. LDR (0.05–0.6 Gy) did not induce significant biological damage in the lung ( Sypin et al, 2003 ; Kim et al, 2007 ; Jangiam et al, 2018 ; Puukila et al, 2019 ). Although many studies opposed it through showing LDR (0.1 and 0.2 Gy) reportedly promoted cell death, inflammation, ROS generation (lipid oxidation), and DNA damage (5-hydroxymethylcytosine); and activated damage responses (p53, p38, p21, ERK1/2, NF-κB, TGF-β, etc.)…”
Section: The Organ-specific Effects Of Ldr In Cell and Mouse Modelsmentioning
confidence: 99%
“…The authors found that the number of cell death, DNA damage, and in ammation response did not signi cantly change in bone marrow, lungs, and testis of mice that were exposed to 0.05 Gy of 137 Cs gamma rays, when compared to a sham control. In contrast, signi cant changes in the number of cell death, DNA damage, and in ammation responses were shown in bone marrow, lungs, and testis of mice that had been exposed to 0.1 and 1.0 Gy of 137 Cs gamma rays [24]. It should be noted that there was a difference in biological response to 0.05 Gy of gamma rays, when compared to 0.1 or 1.0 Gy exposure.…”
Section: Introductionmentioning
confidence: 82%